Răspuns :
√1296 = 36
13 + 36 = 49
√49=7
7 / x = ( 27 - 9 - 3 -1) / (√23+√1618)
7 / x = 14 /(√23+√1618)
x = (√23+√1618) /2
13 + 36 = 49
√49=7
7 / x = ( 27 - 9 - 3 -1) / (√23+√1618)
7 / x = 14 /(√23+√1618)
x = (√23+√1618) /2
[tex]\displaystyle \frac{ \sqrt{13+ \sqrt{1296} } }{x} = \frac{3^3-3^2-3-3^0}{ \sqrt{23+ \sqrt{1618} } } \\ \\ \frac{ \sqrt{13+36} }{x} = \frac{27-9-3-1}{ \sqrt{23+ \sqrt{1618} } } \\ \\ \frac{ \sqrt{49} }{x}= \frac{14}{ \sqrt{23+ \sqrt{1618} } } \\ \\ \frac{7}{x} = \frac{14}{ \sqrt{23+ \sqrt{1618} } } \\ \\ 14x=7\left( \sqrt{23+ \sqrt{1618} } \right) \\ \\ x= \frac{7\left( \sqrt{23+ \sqrt{1618} } \right) }{14} \\ \\ x= \frac{ \sqrt{23+ \sqrt{1618} } }{2} [/tex]